Seed transformation of morinda citrifolia via agrobacterium tumefaciens - Fazliza, Mohd. Ali (Universiti Malaysia Sarawak, UNIMAS, 2008)
Morinda citrifolia, known commercially as noni, is considered as a medicinal plant with various therapeutic values. The significant values of this plant lead an attempt to produce a better plant by introducing foreign genes to the plant through transformation. Prompted by successes in earlier studies of Agrobacterium-mediated in planta transformation procedures in Arabidopsis, similar approach is applied to transform M. citrifolia. This study aims to carry out Agrobacteriummediated in planta transformation on M. citrifolia by using seed transformation method and also to reconstruct transformation vector carrying a novel promoter. The presence of the GUS fragment that has been detected by PCR using GUS-e primers suggests that this plant has been successfully transformed. However, an attempt for reconstructing vector with the novel promoter was unsuccessful.